CONFIGURATION OF THE CONCENTRATION SIMPLEXES OF MULTICOMPONENT SYSTEMS - L. A. Serafimov; A. V. Frolkova; G. A. Semin (Тонкие химические технологии, 2013)
The article deals with the configuration of the concentration simplexes of multicomponent mixtures and its different representations. The analysis of the phase diagram of a five-component mixture was made.